Iron Overload in Chronic Kidney Disease: Less Ferritin, More T2*MRI - Nashwan, Abdulqadir J.; Yassin, Mohamed A.; Mohamed Ibrahim, Mohamed Izham; Abdul Rahim, Hanan F.; Shraim, Mujahed (Frontiers in Medicine, 2022)
To date, there is no consensus on the most reliable marker of iron status in patients with chronic kidney disease (CKD). Serum ferritin is used routinely, although it may be a misleading marker for iron overload. The success of T2* MRI in monitoring iron overload in patients with hemoglobinopathies can be beneficial to monitoring patients with CKD.